Chitosan-Based Nanogel Enhances Chemotherapeutic Efficacy of 10-Hydroxycamptothecin against Human Breast Cancer Cells - Hui Guo; Faping Li; Heping Qiu; Qi Zheng; Chao Yang; Chao Tang; Yuchuan Hou (International Journal of Polymer Science)
Chitosan (CS), the second most abundant polysaccharide in nature, has been widely developed as a nanoscopic drug delivery vehicle due to its intriguing characteristics. In this work, a positively charged CS-based nanogel was designed and synthesized to inhibit the proliferation of breast cancer cell lines. The model drug of 10-hydroxycamptothecin (HCPT) was entrapped into the core via a facile diffusion to form CS/HCPT. The characteristics of CS/HCPT were evaluated by assessing particle size, drug loading content, and drug loading efficiency. Furthermore, cell internalization, cytotoxicity, and apoptosis of CS/HCPT were also investigated in vitro. The present investigation indicated that the positively charged CS-based nanogel could be potentially used as a promising drug delivery system.